Atomistic modeling study of a strain-free stress driven grain boundary migration mechanism. (June 2017) - Wan, Liang; Ishii, Akio; Du, Jun-Ping; Han, Wei-Zhong; Mei, Qingsong; Ogata, Shigenobu
Abstract: A recent experiment (Scripta Mater., 65:990, 2011) shows that the Σ7 {132}/{132} grain boundary in Al can migrate under external stress but produces no strain. Here, based on a bi-crystallographic analysis, an atomic shuffling path was identified as the feasible mechanism for this grain boundary migration. By a density functional theory calculation, it reveals that the enthalpy barrier of this atomic shuffling path increases by external shear stress applied with shear of the grain boundary along the tilt axis 〈111〉, which is in good agreement with experimentally measured shear-direction-dependence of activation enthalpy for this grain boundary migration. Graphical abstract: